A secure collaborative web-based environment for virtual organisations. (23rd March 2009) - Laborde, Romain; Kamel, Michel; Wazan, Samer; Barrere, Francois; , Abdelmalek Benzekri
The concept of the Virtual Organisation (VO) is a natural outcome of network evolution and the growth of collaborative work tools. In the projects Value Improvement thought a Virtual Aeronautical Collaborative Enterprise (VIVACE) and Transglobal Secure Collaboration Program (TSCP), we studied the different issues when setting VOs up. In this paper, we expose the requirements and characteristics of VOs through a use case where the partners produce a technical aeronautic specification, which was proposed by those consortiums. Then, we present a secured collaborative environment that we have deployed to deal with VO security constraints. It combines attribute-based access control models, privileges management infrastructure and identity federation to make VOs more dynamic.